ANALYZING THE RELATIONSHIP BETWEEN EARNINGS MANAGEMENT PRACTICES AND CORPORATE GOVERNANCE STRUCTURES - Riana, Nia; Ruchiyat, Endang; Matriadi, Faisal (Yayasan Kreatif Indonesia Emas, 2024)
Earnings management has been a focal point in corporate finance and accounting due to its potential to distort financial reporting and mislead stakeholders. This study examines the relationship between earnings management practices and corporate governance structures. The aim is to explore how corporate governance mechanisms, such as board composition, ownership structure, and audit quality, influence the likelihood and extent of earnings management. Using a mixed-method approach combining quantitative data analysis and qualitative case studies, the study investigates firms listed in emerging markets over a five-year period. Results reveal that strong corporate governance structures significantly mitigate earnings management practices. However, variations are observed across industries, suggesting the interplay of sector-specific dynamics. These findings underline the critical role of robust governance frameworks in promoting financial transparency and accountability. Keywords: Earnings Management, Corporate Governance, Financial Reporting, Audit Quality Background Earnings management, the deliberate manipulation of financial statements to achieve specific financial results, remains a pervasive issue globally. Despite the adoption of international accounting standards, earnings management practices are often employed to meet market expectations or contractual obligations. On the other hand, corporate governance structures are designed to ensure the accountability of management to shareholders and other stakeholders, thereby curbing unethical financial practices. The relationship between these two elements has been widely debated in academic and professional circles. This study builds on existing literature by examining the role of various governance mechanisms, including board independence, ownership structure, and audit quality, in curbing earnings management in firms operating within emerging markets. Aims This research aims to: Analyze the extent to which corporate governance mechanisms influence earnings management practices. Identify the most effective governance structures in minimizing earnings manipulation. Offer insights into industry-specific dynamics affecting the governance-earnings management relationship. Research Method This study employs a mixed-method research approach: Quantitative Analysis: A longitudinal dataset of 500 firms from emerging markets over five years (2017–2022) is analyzed using regression models to assess the impact of corporate governance variables on earnings management. Qualitative Case Studies: In-depth interviews with board members and auditors from 15 selected firms complement the quantitative findings, offering nuanced perspectives on governance practices. Results and Conclusion The analysis highlights that: Board Independence: Firms with higher proportions of independent directors are less likely to engage in earnings management. Ownership Concentration: Companies with dispersed ownership exhibit higher levels of earnings manipulation compared to those with concentrated ownership. Audit Quality: The presence of Big Four auditors significantly reduces earnings management practices. These findings emphasize the importance of holistic corporate governance frameworks tailored to the unique challenges of emerging markets. Contribution This study contributes to the body of knowledge by providing empirical evidence on the governance-earnings management nexus in emerging markets. It underscores the importance of regulatory reforms and best practices to strengthen corporate governance and enhance financial reporting integrity.